Vulnerabilidad sísmica del Puente Infiernillo II - Galván Chávez, Arturo (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
The “Infiernillo II” bridge, located in the state of Michoacán, is the first bridge in Mexico with a seismic protection system formed for multirotational isolators located on piles and abutments. The importance of the structure justifies the seismic vulnerability assessment. “The seismic vulnerability is an intrinsic property of the structure described by a law cause-effect where the cause is the earthquake and the effect is the damage, (Sandi, 1986). The vulnerability model presented in this study contemplated several stages related with the demand and capacity, which are described below. In the first stage the demand model was developed. This consisted on the selection of an important group of accelerograms recorded on the subduction source of Mexico and another set of signals recorded on the inslab seismic sources of the country. Elastic response spectra and density functions of the demand were calculated. The second stage consisted on determining the capacity model, which was determined starting from a structural model used previously by Aguilar and Jara (2006). It was considered that the damage could occur in the isolation system or in the cylinders of the bridge, specifically in the inferior part of these elements. The moment curvature curves and moment rotation curves were obtained in the inferior part of the piles and later on, with base in analysis push-over, the capacity of the bridge was determined. To conclude, fragility curves were determined. These curves were obtained using the two previous models, based on evaluating the probability that damage exceeds a given state of damage, as a function of the bridge displacements and the peak ground acceleration (PGA); these curves were generated assuming that the demand and the capacity are random variables described by a lognormal density function.

El puente Infiernillo II, ubicado en el estado de Michoacán, es el primer puente en México con un sistema de protección sísmica consistente en aisladores multirrotacionales sobre pilas y estribos. Por esta razón, es importante cuantificar la vulnerabilidad sísmica de esta estructura. “La vulnerabilidad sísmica es una propiedad intrínseca de la estructura descrita a través de una ley causa-efecto donde la causa es el sismo y el efecto es el daño (Sandi, 1986)”. El modelo de vulnerabilidad presentado en este trabajo contempló varias etapas relacionadas con la demanda y la capacidad, las cuales se describen a continuación: En la primera etapa se desarrolló el modelo de demanda. Este consistió en la selección de un conjunto importante de registros sísmicos, tanto de fuentes sísmicas de subducción como de fallamiento normal, que podrían eventualmente afectar al puente. Se calcularon espectros de respuesta elásticos y funciones de densidad de la demanda. La segunda etapa consistió en determinar el modelo de capacidad, el cual se determinó a partir de un modelo estructural utilizado previamente por Aguilar y Jara (2006). Se consideró que el daño ocurre en el sistema de aislamiento o en los cilindros del puente, específicamente en la parte inferior de estos elementos. Se obtuvieron las curvas momento curvatura y momento rotación en las parte inferior de la pilas y posteriormente, con base en análisis push-over, se determinó la capacidad del puente. Para finalizar, se determinaron curvas de fragilidad. Estas se obtuvieron con la ayuda de los dos modelos anteriores con base en evaluar la probabilidad que un daño exceda un estado de daño dado, en función de desplazamientos y de la aceleración máxima del suelo; estas curvas se generaron asumiendo que tanto la demanda como la capacidad se distribuyen de acuerdo con una función de densidad log-normal.
Facultad de Ingeniería Civil. Maestría en Ingeniería en el Área de Estructuras
Keywords: info:eu-repo/classification/cti/7; FIC-M-2008-0025; Vulnerabilidad; Sísmica; Puentes; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4019